A screening of inhibitors targeting the receptor kinase FERONIA reveals small molecules that enhance plant root immunity. Issue 1 (9th October 2022) - Liu, Hong‐Bin; Li, Xiaoxu; Cai, Jun; Jiang, Ling‐Li; Zhang, Xin; Wu, Dousheng; Wang, Lifeng; Yang, Aiguo; Guo, Cun; Chen, Jia; Pu, Wenxuan; Yu, Feng
Summary: Receptor‐like kinases (RLKs) constitute the largest receptor family involved in the regulation of plant immunity and growth, but small‐molecule inhibitors that target RLKs to improve agronomic traits remain unexplored. The RLK member FERONIA (FER) negatively regulates plant resistance to certain soil‐borne diseases that are difficult to control and cause huge losses in crop yields and economy. Here, we identified 33 highly effective FER kinase inhibitors from 1494 small molecules by monitoring FER autophosphorylation in vitro . Four representative inhibitors (reversine, cenisertib, staurosporine and lavendustin A) inhibited the kinase activity of FER and its homologues in several crops by targeting the conserved ATP pocket in the kinase structure. FER contributes to the physiological impact of representative inhibitors in plants. The treatment of roots with reversine, staurosporine and lavendustin A enhanced innate immunity in plant roots and thus alleviated soil‐borne diseases in tobacco, tomato and rice without growth penalties. Consistently, RNA sequencing assays showed that lavendustin A and reversine exert profound impacts on immunity‐related gene expression. Our results will set a new milestone in the development of the plant RLK kinase regulation theory and provide a novel strategy for the prevention and control of plant soil‐borne diseases without growth penalties.